2019
DOI: 10.1021/acs.langmuir.9b02335
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Crystalline Suspensions of Photosensitive Paramagnetic CeF3 Nanodiscs

Abstract: The design of high-performance energy-converting materials is an essential step for the development of sensors but the elaboration of the bulk materials currently used remains costly and difficult. Therefore, a different approach based on the self-assembly of nanoparticles has been explored. We report on the preparation by solvothermal synthesis of highly crystalline CeF 3 nanodiscs. Their surface modification by bisphosphonate ligands led to stable, highly concentrated, colloidal suspensions in water. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Similar SAXS profiles suggesting two short-range orders were previously observed in columnar nematic phases for plate-like particles such as Al(OH) 3 nanoplates, 39 Sb 3 P 2 O 14 3− nanosheets, 40 and CeF 3 nanodisks. 42 A Schlieren texture similar to that in Fig. 4b was also observed by POM in a columnar nematic phase of lyotropic discotic liquid crystals.…”
Section: Resultssupporting
confidence: 68%
“…Similar SAXS profiles suggesting two short-range orders were previously observed in columnar nematic phases for plate-like particles such as Al(OH) 3 nanoplates, 39 Sb 3 P 2 O 14 3− nanosheets, 40 and CeF 3 nanodisks. 42 A Schlieren texture similar to that in Fig. 4b was also observed by POM in a columnar nematic phase of lyotropic discotic liquid crystals.…”
Section: Resultssupporting
confidence: 68%
“…So, for CeF3 NCs synthesized at 160 °C, the PL emission spectrum consists of two bands with PL maxima at 361 nm and 500 nm. The PL band at "perturbed" Ce 3+ [26,42,43]. At the same time, for CeF3 NCs synthesized at 230 °C, the PL emission spectrum is represented by a single band with a maximum at 381 nm.…”
Section: Optical Properties Of Cef3 Ncs Prepared At Different Tempera...mentioning
confidence: 93%
“…The magnetic behavior of CeF 3 crystals was studied relatively little and was described with the help of several models: the theory of a crystalline field [52], the mixed valence Ce 3+ -Ce 4+ behavior [53] and the superexchange interaction of cerium ions [54]. The study at T 50 K showed abnormal magnetic susceptibility behavior in CeF 3 nanodisks, which was explained by defects and/or dimensional effects [55]. Work [56] reports on the structural, magnetic, and optical properties of Tb 3+ -doped CeF 3 nanocrystals prepared via a polyol-assisted route, followed by calcinations.…”
Section: Introductionmentioning
confidence: 99%